2019
DOI: 10.1097/md.0000000000017989
|View full text |Cite
|
Sign up to set email alerts
|

High internal radiation exposure associated with low socio-economic status six years after the Fukushima nuclear disaster

Abstract: Rationale: Managing the health of vulnerable groups is an important component of health care. Given the long-term burden of radiation-release incidents among those exposed, managing the health of vulnerable groups following a nuclear disaster is very important. However, there is limited information available concerning the long-term management of the health effects of radiation exposure in vulnerable groups following nuclear disasters. After the Fukushima Daiichi Nuclear Power Plant (FDNPP) acciden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…The health status of elderly people, as well as sick and/or hospitalised people, may also be particularly affected by the disturbances due to the event and the protective actions. Homeless people may also receive more exposure because of their poor living conditions (Sawano et al., 2019). Therefore, the Commission recommends the identification of vulnerable groups and their consideration in the implementation of the principle of optimisation. (68) In order to reduce individual exposures and limit inequities in the distribution of exposures, the Commission recommends using reference levels to guide the optimisation of protection during the successive phases of a nuclear accident.…”
Section: General Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The health status of elderly people, as well as sick and/or hospitalised people, may also be particularly affected by the disturbances due to the event and the protective actions. Homeless people may also receive more exposure because of their poor living conditions (Sawano et al., 2019). Therefore, the Commission recommends the identification of vulnerable groups and their consideration in the implementation of the principle of optimisation. (68) In order to reduce individual exposures and limit inequities in the distribution of exposures, the Commission recommends using reference levels to guide the optimisation of protection during the successive phases of a nuclear accident.…”
Section: General Considerationsmentioning
confidence: 99%
“…The health status of elderly people, as well as sick and/or hospitalised people, may also be particularly affected by the disturbances due to the event and the protective actions. Homeless people may also receive more exposure because of their poor living conditions (Sawano et al., 2019). Therefore, the Commission recommends the identification of vulnerable groups and their consideration in the implementation of the principle of optimisation.…”
Section: General Considerationsmentioning
confidence: 99%
“…There is reason to discuss explanations regarding the finding that the group characterized by low education was least likely to move from the remediation area and that individual income was associated with lower concern over radiation risk-two results that were clear and statistically significant for all the controls. Previous studies have found that low income implies greater exposure to hazards, limited protection, limited choice (Hunter 2005;Link et al 1993;Sawano et al 2019;Taylor et al 1997), and generally higher levels of distress due to financial strain (Linander et al 2014), all adding to perceptions of the world as more dangerous and worrisome. We might understand the risk attitudes among the wealthy as resulting from their experience of greater control over their current and future situation and seeing the world as relatively safe.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, risk attitudes cannot be dismissed as irrational or excessive risk aversion but should be regarded as cognitions embedded and conditioned in a social context. Indeed, data point to a higher degree of actual vulnerability to various environmental hazards among those characterized by low SES (Hunter 2005), including radiation (Sawano et al 2019), most likely because they face more dangerous working conditions (Link et al 1993) and living environments (Taylor et al 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, TS also employed a bottom-up approach for key health issues following the 2011 triple disaster such as the health of decontamination workers (Sawano et al, 2016a(Sawano et al, , 2016b(Sawano et al, , 2018a(Sawano et al, , 2020. Further, he covered some radiological issues using this approach (Sawano et al, 2019a). Needless to say, the clinical care of these patients preceded the publication of their case reports.…”
Section: Case 2: Summarization and Publications Of Clinical Cases Encmentioning
confidence: 99%